Social Mobility and Perceived Discrimination: Adding an Intergenerational Perspective. (29th October 2018) - Schaeffer, Merlin
Abstract: This article adds an intergenerational perspective to the study of perceived ethnic discrimination. It proposes the conjecture that perceived discrimination tends to increase with parental education, particularly among those children of immigrants who have attained only mediocre levels of education themselves. I discuss that this conjecture may be developed as an argument that comes in two versions: a narrow version about explicit downward (intergenerational) mobility and a wide version about unfulfilled mobility aspirations more generally. Analyses based on the six-country comparative EURISLAM survey support the argument: parental education positively predicts perceived discrimination in general, but among the less educated, this relation is most pronounced, whereas it is absent among those with tertiary education. A replication and falsification test based on the German IAB-SOEP Migration Sample reconfirms the main finding and provides further original pieces of evidence. The analyses suggest processes associated with unfulfilled mobility aspirations as the more plausible underlying reason.